1997
DOI: 10.1016/s1063-4584(97)80013-1
|View full text |Cite
|
Sign up to set email alerts
|

Activation of fibrillar collagen synthesis and phenotypic modulation of chondrocytes in early human osteoarthritic cartilage lesions

Abstract: The objective of this study was to investigate the expression and extracellular distribution of fibrillar collagen types I, II, and III in early stage osteoarthritic cartilage in order to elucidate matrix gene expression and cell differentiation in early phases of the disease. Arthroscopically, derived specimens of early stage osteoarthritic articular cartilage were analyzed by histochemistry, immunohistochemistry and by in situ hybridization and compared with normal articular cartilage samples. In normal arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
56
0
3

Year Published

1998
1998
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 24 publications
3
56
0
3
Order By: Relevance
“…Continued synthesis of CII was clearly reflected in normal ankle cartilage both by in situ hybridization and immunodetection of CPII at all ages from 16 to 75 years. Others (25,26) have shown that mRNA for CIIB was undetectable in normal knee articular cartilage. They also used in situ hybridization but used larger probes than that used for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Continued synthesis of CII was clearly reflected in normal ankle cartilage both by in situ hybridization and immunodetection of CPII at all ages from 16 to 75 years. Others (25,26) have shown that mRNA for CIIB was undetectable in normal knee articular cartilage. They also used in situ hybridization but used larger probes than that used for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Current hypotheses to explain the changes in OA chondrocytes include the notion that phenotypic alterations of the cells occur in response to changing signals or matrix composition (10)(11)(12)(13). It is well known that chondrocytes can adopt different phenotypes, including those associated with the growth plate (resting, proliferating, hypertrophic), those associated with the different zones of AC, and the dedifferentiated phenotype observed in monolayer culture (3,7,13,17).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown that a major change in the chondrocyte phenotype in OA involves a switch in the types of collagen molecules that are synthesized. Clusters of chondrocytes in OA cartilage have been shown to express types I and III collagens, which are not normally found or found at very low levels in normal AC (10,12,(69)(70)(71).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations